State-Owned Enterprises and Endogenous Growth - Matuszak, Piotr (Central European Journal of Economic Modelling and Econometrics, 2023)
This article analyzes the growth impact of state ownership in enterprises by introducing state-owned enterprises (SOEs) into the endogenous, Romer-type economic growth model. We build on the empirical firm-level analysis showing that SOEs underperform their privately owned counterparts and consider SOEs’ inefficiency and related subsidization in the growth model. Our model predicts that the growth rate is decreasing in the SOE inefficiency and SOE shares in final goods production and R&D sectors. The model helps to shed light on the mechanisms behind empirical facts observed in European economies in the 21st century - lower growth and innovation rates in countries with larger SOE shares.